Handbook of laser welding technologies - Katayama, S. (Seiji) (Woodhead Publishing series in electronic and optical materials., 2013)
Laser welding is a rapidly developing and versatile technology which has found increasing applications in industry and manufacturing. It allows the precision welding of small and hard-to-reach areas, and is particularly suitable for operation under computer or robotic control. This book reviews the latest developments in the field and how they can be used across a variety of applications.